Probing the Relationship Between Home Numeracy and Children's Mathematical Skills: A Systematic Review - Mutaf-Yıldız, Belde; Sasanguie, Delphine; De Smedt, Bert; Reynvoet, Bert (Frontiers in Psychology, 2020)
The concept of home numeracy has been defined as parent-child interactions with numerical content. This concept started to receive increasing attention since the last decade. Most of the studies indicated that the more parents and their children involve in numerical experiences, the better children perform in mathematical tasks. However, there are also contrasting results indicating that home numeracy does not play a role or that there is a negative association between the parent-child interactions and children’s math performance. To shed light on these discrepancies, a systematic review searching for available articles examining the relationship between home numeracy and mathematical skills was conducted. Thirty-seven articles were retained and a p-curve analysis showed a true positive association between home numeracy and children’s mathematical skills. A more qualitative investigation of the articles revealed five common findings: (1) Advanced home numeracy interactions but not basic ones are associated with children’s mathematical skills. (2) Most participants in the studies were mothers, but when both parents participated and were compared, it was mothers’ but not fathers’ formal home numeracy activities (i.e., explicit numeracy teaching) that were linked with children’s mathematical skills. (3) Formal home numeracy activities have been investigated more commonly than informal home numeracy activities (i.e., implicit numeracy teaching). (4) The number of studies that have used questionnaires to assess home numeracy is larger compared to the ones that have used observations. (5) The majority of the studies measured children’s mathematical skills with comprehensive tests that index mathematical ability with one composite score rather than with specific numerical tasks. These five common findings seem to play a role in the contradictory results regarding the relationship between home numeracy and mathematical skills. Therefore, more research is necessary to draw quantitative conclusions about these five points.